Dynamics of Algeria’s Natural Gas Sector: An Econometric Assessment Using the ARDL Approach (1999–2023) - Ahmaed, Dr. Belkheir Larbi; Abdelkamel, Dr. Belahbib (Journal of Ecohumanism, 2025)
The study examined the dynamics of Algeria’s natural gas sector from 1990 to 2023, focusing on the effects of domestic production and local consumption on exports using the ARDL model. Unit root tests (ADF) showed that all variables are stationary at first difference, I(1), while the Bounds Test confirmed a long-term cointegration relationship among them. The Error Correction Model revealed a negative and significant adjustment coefficient of -0.75, indicating that 75% of short-term deviations are corrected annually. In the short term, gas production positively influenced exports by 0.60%, whereas domestic consumption had a negative effect of 1.11%. In the long term, production maintained a positive and significant impact of 0.81% on exports, while consumption had a small, negative, and statistically insignificant effect (0.22%). These findings suggest that expanding production capacity and rationalizing domestic consumption are crucial for sustaining Algeria’s gas exports. The results provide practical insights for policymakers to design effective strategies for balancing domestic energy needs with export growth.